ZAWARCIE UMOWY PRZEDWSTĘPNEJ W OBROCIE NIERUCHOMOŚCIAMI - Mróz, Arkadiusz (Zeszyty Prawnicze, 2016)
THE CONCLUSION OF A PRELIMINARY CONTRACT IN CONVEYANCING Summary This is the first of three articles presenting a detailed discussion of the structure and functions of the preliminary contract (umowa przedwstępna), its significance, and the practical potential for its use in conveyancing. This article shows the essence of the preliminary contract as a particular type of pre-contractual agreement and its relation to the final contract (umowa stanowcza). The study discusses issues related to the content of the preliminary contract, methods of concluding such a contract by the parties, as well as the term for the conclusion of the final contract. <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />